2014
DOI: 10.2147/opth.s61342
|View full text |Cite
|
Sign up to set email alerts
|

Fornix-based versus limbal-based conjunctival flaps in trabeculectomy with mitomycin C in high-risk patients

Abstract: PurposeTo compare the surgical outcomes of limbal-based and fornix-based trabeculectomy in eyes with a history of ocular incisional surgery.MethodsTwenty-six eyes underwent limbal-based trabeculectomy (group LB), and were condition matched with 26 eyes that received fornix-based trabeculectomy (group FB). Surgical failure was recorded retrospectively if the intraocular pressure value was either ≥21, ≥18, and ≥15 mmHg (conditions A, B, and C, respectively) or <4 mmHg or if the patient required additional glauco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…As reported by Solus et al 25 and Kuroda et al, 36 some reports compared LB and FB groups for surgical success and reported no significant difference. Yokota et al 37 reported in a prospective study a significantly higher surgical failure rate in the FB group than in the LB group of patients with open angle glaucoma.…”
Section: Discussionmentioning
confidence: 89%
“…As reported by Solus et al 25 and Kuroda et al, 36 some reports compared LB and FB groups for surgical success and reported no significant difference. Yokota et al 37 reported in a prospective study a significantly higher surgical failure rate in the FB group than in the LB group of patients with open angle glaucoma.…”
Section: Discussionmentioning
confidence: 89%
“…Most prior studies have also documented similar IOP control between the limbus-based and fornix-based conjunctival incisions. [ 6 15 16 17 18 19 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that bleb leaks occurred more frequently in fornix-based trabeculectomy but cannot be used for limbal-based trabeculectomy [26, 27]. Meanwhile, other reports found no difference about bleb leak between these two groups [28, 29]. A recent systematic review also reported that there was similar efficacy with respect to IOP control and bleb failure (including bleb leak) in both types of conjunctival flap incisions [30].…”
Section: Discussionmentioning
confidence: 99%